Naturaleza jurídica del ejercicio acumulado de la acción civil a la acción penal conforme al nuevo Código Procesal Penal Peruano - Hurtado Poma, Juan Rolando (2022)
This thesis deals with a topic of criminal procedural law. Referred to the legal nature of the accumulated exercise of civil action to criminal action under the new Peruvian criminal procedure code. In this sense, I will answer what is the proper interpretation and scope of article twelve, third numeral of the Peruvian criminal procedure. For such case I analyze historical, normative, jurisprudential aspects and get to propose a appropriate interpretation and moose of the emerging civil responsibility of a fact with criminal appearance.